Plasma and soft tissue pharmacokinetics of ceftolozane/tazobactam in healthy volunteers after single and multiple intravenous infusion: a microdialysis study. (29th May 2021) - Al Jalali, V.; Wölfl-Duchek, M.; Taubert, M.; Matzneller, P.; Lackner, E.; Dorn, C.; Kratzer, A.; Wulkersdorfer, B.; Österreicher, Z.; Zeitlinger, M.
Abstract: Objectives: To investigate ceftolozane/tazobactam pharmacokinetics (PK) in plasma and interstitial space fluid (ISF) of muscle and subcutaneous tissue and establish a population PK model. Methods: Eight healthy volunteers received four IV doses of 1000/500 mg ceftolozane/tazobactam q8h in a prospective, open-labelled PK study. ISF concentration–time profiles were determined via in vivo microdialysis up to 8 h post-dose and efficacy of unbound ceftolozane and tazobactam was estimated using the time above MIC (%ƒ T >MIC ) and time above threshold concentration (% T >CT ), respectively. A population PK model was established by merging derived plasma and soft tissue PK data. Results: Ceftolozane reached %ƒ T >MIC values of 100% in plasma, muscle and subcutaneous ISF for Enterobacteriaceae and 87%, 89% and 87%, respectively, for Pseudomonas aeruginosa . Tazobactam % T >CT was 21%, 22% and 21% in plasma, muscle and subcutaneous ISF, respectively. Plasma protein binding was 6.3% for ceftolozane and 8.0% for tazobactam. Multiple-dose ceftolozane AUC0–8 ISF/plasma ratios were 0.92 ± 0.17 in muscle and 0.88 ± 0.18 in subcutis, and tazobactam ratios were 0.89 ± 0.25 in muscle and 0.87 ± 0.21 in subcutis, suggesting substantial soft tissue penetration. Conclusions: Tazobactam % T >CT values were distinctly below proposed target values, indicating that tazobactam might be underdosed in the investigated drug combination. However, ISF/unbound plasma ratios of ceftolozane and tazobactam support their use in soft tissue infections. A plasma and soft tissue PK model adds important information on the PK profile of ceftolozane/tazobactam. Further investigations in patients suffering from wound infections are needed to confirm these findings.